Potmarks on Early Dynastic and Old Kingdom Bread Moulds from the Settlement Layers of Tell el-Murra - Kazimierczak, Magdalena (Études et Travaux, 2024)
Early Dynastic and Old Kingdom bread moulds belong to the type of vessels on which potmarks appear the most often, which is a phenomenon recorded during works conducted at different sites. Excavations carried out at the Tell el-Murra between 2011 and 2019 produced a significant number of vessels of this type with various marks. This paper is devoted to the 118 pre-firing marks from Early Dynastic and Old Kingdom bread moulds from the settlement layers at the Tell el-Murra. The paper comparatively analyses marks from two subsequent chronological periods, with the aim to test the validity of theories regarding their function and meaning, based on examples from Tell el-Murra. The study concludes that the high frequency of potmarks on bread forms was not accidental, but related to certain economic processes and changes, as also indicated in this paper.